Pengaruh Simplisia Bunga Kenanga (Cananga odorata (Lamk). Hook.) sebagai Mat Elektrik Terhadap Knock-Down Nyamuk Aedes Aegypti - anik nuryati; siti nuryani; Andreaddo doni wibowo (Medical Laboratory Technology Journal, 2015)
Abstract: The main vector of dengue fever is Aedes aegypti. Ylang flower can be useful as an anti-mosquito, so in this study ylang flower botanicals chosen as rechargeable electric mat as an anti-mosquito Aedes aegypti. Objectives Determine the effect of various heavy and heavy crude drugs effective of ylang flowers (Cananga odorata (lamk.) Hook.) as an electric mat, the number of Aedes aegypti percentage knock-down of various heavy crude drugs ylang flowers. Methods This research uses experimental research with Post test with control. The results obtained from counting the number of knock-down mosquitoes Aedes aegypti after 1 hour exposure to various heavy simplisia ylang flowers are 1 g, 1,5 g, 2 g, 2,5 g, 3 g and 3,5 g. Results Ylang flowers as electricalmat having a knock-down effect on the mosquito Aedes aegypti. The mean effect of knock-down mosquitoes produced heavy crude drugs in 1 g, 1,5 g, 2 g, 2,5 g, 3 g and 3,5 g of 2,0, 2,75, 4,75, 6,0, 7,75 and 9,0. Conclusion Ylang flowers simplicia as electric mat influence 90.6% of the knock-down mosquito Aedes aegypti. The mean effect of knock-down mosquitoes produced heavy crude drugs in 1 g, 1.5 g, 2 g. 2.5 g, 3 g and 3.5 g of 2.0, 2.75, 4.75; 6.0; 7.75 and 9.0 and obtained the effective weight of 3.5 grams. The percentage knock-down mosquitoes in heavy crude drugs ylang flowers 1 g, 1.5 g, 2 g, 2.5 g, 3 g, and 3.5 g were 10%, 13.75%, 23.75%, 30%, 38.75%, and 45%